2003
DOI: 10.1088/0953-8984/15/46/019
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of diamond nanocrystals from catalysed carbon black in a high magnetic field

Abstract: Under a static high magnetic field of 10 T, diamond-like carbon (DLC) nanocrystals and graphite-coated n-diamond nanoparticles have been synthesized after a pyrogenation of carbon black and a nanometre-sized iron catalyst at atmospheric pressure and a temperature of 1100 °C. The product is analysed by x-ray diffraction, Raman spectroscopy, transmission electron microscopy and electron-probe microanalysis. The average size of the DLC nanopowders is about 20 nm, and that of the graphite-coated n-diamond particle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(31 citation statements)
references
References 28 publications
1
30
0
Order By: Relevance
“…At the same time, it is improved that the static magnetic field will cause the non-uniform deposition on the substrates [8]. Meanwhile, the declining of the surface free energy of diamond films also plays an important role in depositing process [9,17], and the increase in the growth rate of diamond films may attribute mainly to the combined affection of the magnetic field and thermal pyrolysis. …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…At the same time, it is improved that the static magnetic field will cause the non-uniform deposition on the substrates [8]. Meanwhile, the declining of the surface free energy of diamond films also plays an important role in depositing process [9,17], and the increase in the growth rate of diamond films may attribute mainly to the combined affection of the magnetic field and thermal pyrolysis. …”
Section: Resultsmentioning
confidence: 99%
“…It is reported by Wen et al [9] and Little et al [10] recently that diamond film can be deposited under static magnetic field (MF) with an intensity of 10-20 T. Both of them reported that diamond nanoparticles can be synthesized from carbon black under a static high magnetic field, and the yield of diamond increased by 30% with the presentation of magnetic field. According to their analysis, the magnetic field can reduce the surface energy of diamond, and promote the growth rate of diamond film.…”
Section: Introductionmentioning
confidence: 99%
“…The observed d spacings (Table 11) showed a good match with those for n-diamond. Table 11 Comparison of d spacing for n-diamond produced by CVD in high magnetic field 32 with standard data and previous CVD study, 29 …”
Section: Explosive Detonation 22mentioning
confidence: 99%
“…[29][30][31] It is noteworthy that the lattice constant of the high temperature c-Fe allotrope (,0 . 365 nm) 80 is close to those of diamond and n-diamond.…”
Section: First Principles Computationsmentioning
confidence: 99%
“…It is worth noting that a new allotrope of carbon, socalled n-diamond [32][33][34][35][36][37] , exhibits a distinct diffraction peak around 50.8 o that very closed to the main peak of these new carbon polymorphs. For comparison, a typical experimental XRD spectra found in Fe-catalyzed carbon black heat treatment at 1400…”
mentioning
confidence: 99%